ANALISIS PERHITUNGAN HPP FULL COSTING DAN HARGA JUAL COST PLUS PRICING PADA UD ARPUMA NGANJUK - Purnama Putri, Intan; Puji Winarko, Sigit; Astuti, Puji (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine and analyze the calculation of the cost of goods manufactured (HPP) and the selling price applied by the company and the calculation using full costing and cost plus pricing at UD Arpuma. The benefit of this difference in calculations is that by calculating using full costing and cost plus pricing, the company will get the right price as well as there is a clear calculation basis in accordance with the theory used. The approach and type of research used is descriptive quantitative. The data analysis technique used is full costing and cost plus pricing. The results showed that the full costing and cost plus pricing krecek uyel methods resulted in lower HPP and selling prices because the company only used estimates in determining prices. Meanwhile, krecek plates resulted in lower HPP and higher selling prices. This is because the full costing and cost plus pricing methods detail all the costs incurred, thus obtaining a higher price. However, overall the price set by the company is still high compared to using the full costing and cost plus pricing methods. It is expected that UD Arpuma will use the full costing and cost plus pricing method because it produces a more precise price.